Hubungan Analisis Ratio Keuangan dengan Kesehatan Perusahaan - Soekarso Soekarso (The Winners, 2009)
In the business world, companies develop a vision and mission to improve welfare in the future. The work program the company is to achieve productivity and profitability. Finance in the company is one of the strategic functions that includes wealth management and transformation of added value (added value) and also the control of corporate health. The financial statements such as balance sheet (balance sheet), profit and loss statement (income statement), and financial ratio (financial ratios), reflects the company's performance and health. Financial ratio analysis relates to the health of the company through a ratio of effectiveness, efficiency, productivity, profitability, liquidity, and solvability. Analysis shows that whenever actual value of financial ratios is above standard it means the company is healthy, and when the actual value of financial ratios is below the standard, it reversely means that companies are not healthy.